Division, Persecution and Rearrangement - The AKP’s Controversial Relationship with Turkish Civil Society - Turkmen, Seref (European Scientific Journal, ESJ, 2023)
Throughout history, and especially in the Ottoman Empire, Turkish culture has attached great importance to foundations. In the past, mosques, schools, public baths, free kitchens, and hospitals alike, all operated in the form of foundations. After the proclamation of the republic in 1923, much of this structure was abolished by the state founder Mustafa Kemal Ataturk because he believed that they were tied to the Muslim clergy by a thousand threads. In the initial period of the republic, Turkish civil society was slowly reorganized following Western examples. It lived its second heyday as a result of the introduction of the new constitution in 1982 and Turgut Ozal’s liberal economic policy, and his media market liberalization after 1983. After the Justice and Development Party came to power in 2002, the civil society in Turkey was significantly rearranged. Recep Tayyip Erdogan’s party favored some with a system of opportunities, and sued those who put the government in a politically awkward position. Building on some of the scandalous cases of the second half of 2010s, this article seeks to explain the current situation of Turkish civil society and the conflicts that characterize it. The article highlights the campaign against Amnesty International and the Open Society Foundation, which by November 2021 was only partially over. In the case of current events, in the absence of scientific sources, the writings of renowned Turkish journalists at world-famous news portals were used as a basis. However, in order to substantiate the theory, an abundant literature in Turkish and English was also used.